Elasticity of Growth in the Processing Industry Towards the Contribution of Labour Absorption in the Processing Industry in the City of Palu - Alfiana, Alfiana; Nurnaningsih, Nurnaningsih; Sading, Yunus; Paembonan, Laendatu; Yohan, Yohan (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The manufacturing sector is a strategic pillar of regional economic development due to its significant role in generating added value and creating employment opportunities. However, in Palu City, the growth of this sector has not consistently translated into proportional increases in employment absorption. This study aims to analyze the elasticity of manufacturing sector growth with respect to its contribution to employment absorption in Palu City over the period 2019–2023. A descriptive quantitative approach was employed, utilizing secondary data obtained from the Central Bureau of Statistics (BPS) of Palu City and relevant agencies. The data set comprises the manufacturing sector’s Gross Regional Domestic Product (GRDP), the number of workers in the manufacturing sector, and the total workforce in Palu City. The analysis involved calculating both output and employment growth rates, followed by the computation of labor absorption elasticity using the elasticity ratio formula. The results reveal that the relationship between manufacturing output growth and employment absorption in Palu City is volatile and not always proportional, as indicated by the elasticity measurements of manufacturing GRDP growth relative to employment growth in the sector. Certain years recorded negative elasticity values, reflecting inverse relationships driven by internal sectoral dynamics such as efficiency gains, technological adoption, and external shocks including the COVID-19 pandemic. The study concludes that although the manufacturing sector makes a substantial contribution to economic growth, its impact on job creation remains suboptimal. As such, integrated policies are needed to align industrial growth with sustainable employment and improve regional welfare.